Economic shocks, progressiveness of taxation, and indexation of taxes and public expenditure in EMU - Markku Kotilainen (The Research Institute of the Finnish Economy (ETLA), 2006)
We study the effects of demand, tax and supply shocks in one- and twocountry macroeconomic models with fixed exchange rates, with our main emphasis on the stabilisation properties of progressive taxation. The models try to depict outcomes for the EMU countries. In the one-country model we obtain a priori results. In the case of the two-country model, we calculate the solution by using realistic estimates for the parameters. In the one-country model progressive taxation tends to stabilise output in the cases of demand and tax shocks. In the case of a supply shock, tax progressiveness tends to stabilise output if taxes are fully indexed. If they are not, the outcome depends especially on the size of the demand effect of taxes. Progressive taxation stabilises prices definitely only in the case of a tax shock. In the cases of demand and supply shocks, the outcome depends in opposite ways on the relative strengths of the demand and supply effects of taxes. In the two-country model progressive taxation tends to increase output stability in both countries in the face of a demand shock. Progressiveness stabilises prices if wages and prices react only modestly to changes in taxes, but destabilises them when these reactions are strong. In the case of a tax shock, progressive taxation tends to stabilise the output and prices of both countries. In the case of a supply shock, output and prices are not very sensitive to progressiveness. When tax indexation is low, progressiveness can, however, destabilise the output of the country where the shock originates. All in all, progressive taxation tends to stabilise output or has a neutral effect in most cases. The effects on price stabilisation are, however, more controversial.
Keywords: E32; E62; E63; E64; F33; F41; F42; 330; Economic and Monetary Union; EMU; Taxation; Public Expenditure; Progressiveness of Taxation; Indexation; Schock; Steuerpolitik; Steuerprogression; Öffentliche Ausgaben; Indexierung; Theorie; Europäische Wirtschafts- und Währungsunion